The Role of Teachers in Improving Student Motivation to Learn - Firdaus, Baynana Nur; Saputra, Briyan Ade; Ardiansyah, Zaky (Proceedings Series on Social Sciences & Humanities, 2025)
In today's digital age, rapid technological developments and the widespread use of social media have had a significant impact on student learning behavior, especially at the high school level. Symptoms such as decreased focus on learning, a tendency to become bored quickly, and dependence on digital entertainment pose serious challenges for the education sector. In such circumstances, teachers play a crucial role in reigniting students' enthusiasm for learning through innovative approaches that align with the dynamics of the times. This study aims to theoretically explore teachers' contributions in fostering students' learning motivation by referencing approaches and strategies examined through literature reviews. The method used is literature review (library research), analyzing various scientific sources such as books, journals, and relevant research findings on similar topics. The findings from this study indicate that teachers who apply interactive learning methods, build good communication with students, and utilize technology wisely have great potential to increase learning motivation. From these results, it can be concluded that teachers' ability to adapt to the times and actively serve as mentors and motivators is essential to address the learning motivation crisis among high school students.